Behavioral Settings are Crucial for Assessing Sensorimotor, Anxiety, and Social Changes in Aging and Spinal Cord Injury - Chloé M. Gazard; Nacéra Douich; Eloïse Néel; Patrick Villette; Florence E. Perrin; Yannick N. Gerber (Brain and Behavior)
ABSTRACT Introduction For decades, behavioral tests have been used to evaluate functions and dysfunctions of the central nervous system. The open field test is one of the most commonly used methods to assess murine behaviors, including exploration, spontaneous motor activity, and anxiety‐like behaviors. The choice of open field shape can vary across studies, either to address specific research objectives or to simplify data acquisition and analysis. Methods In this study, we investigated whether the shape of the open field arena influences mice's behaviors in an age‐ and sex‐dependent manner during physiological aging. We then assessed how the shape of the open field influences male mice's behaviors in an age‐dependent manner following spinal cord injury. Results Across physiological aging, we observed that the shape of the open field arena influenced motor activity, anxiety, and social behavior, with some gender differences. Following spinal cord injury, arena shape affected motor activity, tactile sensitivity, and social behavior in male mice, but anxiety‐like behaviors remained unaffected. Conclusion Our results highlight that the shape of the arena significantly influences mouse behavior, emphasizing the importance of careful experimental protocol design in behavioral assessments.